Practice based education to improve delivery systems for prevention in primary care: randomised trial - Margolis, Peter A (BMJ Publishing Group Ltd., 2004)
Objective To examine the effectiveness of an intervention that combined continuing medical education with process improvement methods to implement “office systems” to improve the delivery of preventive care to children. Design Randomised trial in primary care practices. Setting Private paediatric and family practices in two areas of North Carolina. Participants Random sample of 44 practices allocated to intervention and control groups. Intervention Practice based continuing medical education in which project staff coached practice staff in reviewing performance and identifying, testing, and implementing new care processes (such as chart screening) to improve delivery of preventive care. Main outcome measure Change over time in the proportion of children aged 24-30 months who received age appropriate care for four preventive services (immunisations, and screening for tuberculosis, anaemia, and lead). Results The proportion of children per practice with age appropriate delivery of all four preventive services changed, after a one year period of implementation, from 7% to 34% in intervention practices and from 9% to 10% in control practices. After adjustment for baseline differences in the groups, the change in the prevalence of all four services between the beginning and the end of the study was 4.6-fold greater (95% confidence interval 1.6 to 13.2) in intervention practices. Thirty months after baseline, the proportion of children who were up to date with preventive services was higher in intervention than in control practices; results for screening for tuberculosis (54% v 32%), lead (68% v 30%), and anaemia (79% v 71%) were statistically significant (P < 0.05). Conclusion Continuing education combined with process improvement methods is effective in increasing rates of delivery of preventive care to children.